High-performance polysulfone fiber composite diaphragm and preparation method thereof
Through the combination of electrospinning technology and polysulfone block copolymer structure, functionalized polysulfone polymers are introduced to solve the problem of difficulty in balancing the performance of separator materials in the existing technology, and realize high-performance electrolysis of water for hydrogen production. Composite diaphragm.
Patent Information
- Application Number
- CN202411448953.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
AI Technical Summary
The separator materials for electrolysis of alkaline aqueous solutions in the prior art cannot take into account high OH-ion conductivity, low resistivity, high corrosion resistance, high mechanical stability and excellent gas barrier properties, and it is difficult to meet the application needs of large-scale application of electrolytic hydrogen production.
Electrospinning technology is used to form an ordered nanofiber layer, and a polysulfone block copolymer structure is introduced. The introduction of imidazole groups and quaternary ammonium groups provides a basis for OH-ion conduction, forming a hydrophilic and hydrophobic microphase separation morphology to enhance mechanical properties. and dimensional stability.
It achieves high OH-ion conductivity, high gas barrier properties, high mechanical stability and high alkali corrosion resistance, meeting the performance requirements of composite separators for electrolytic water hydrogen production.
Smart Images

Figure CN119332302A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a high-performance polysulfone fiber composite diaphragm and a preparation method thereof. Background Art
[0002] Clean energy hydrogen is an important tool for the green and low-carbon transformation of energy, and an important part of the future national energy system. Green hydrogen produced by electricity generated from renewable energy and then through water electrolysis and other means is an important way to solve the energy and environmental crisis and achieve the dual carbon goals. Among the many hydrogen production methods, hydrogen production by water electrolysis is currently the most effective way to produce green hydrogen on a large scale. The diaphragm is one of the core components of the water electrolysis system. In the electrolyzer, it mainly separates the anode and cathode plates to prevent short circuits and prevents hydrogen and oxygen from mixing with each other to ensure the purity of hydrogen. On the other hand, the diaphragm must allow ions in the solution to pass through to ensure that the electrolysis process continues. The performance of the diaphragm is closely related to the efficiency, hydrogen purity, hydrogen production stability and safety of the electrolyzer.
[0003] The ideal diaphragm material should have the following characteristics: (1) good ion conductivity and low resistivity; (2) high gas barrier and high corrosion resistance; (3) thin thickness and high mechanical strength; (4) good chemical stability and dimensional stability. However, the diaphragm materials for alkaline aqueous solution electrolysis in the prior art cannot take into account the above four aspects of performance and are difficult to meet the large-scale application requirements of water electrolysis hydrogen production. Therefore, the present invention aims to provide a diaphragm material with high OH - Diaphragm materials for hydrogen production by water electrolysis with high ion conductivity, low resistivity, high corrosion resistance, high mechanical stability and excellent gas barrier properties.
[0004] Polysulfone materials have excellent thermal stability, mechanical stability, alkali corrosion resistance, good electrical conductivity and other properties, and are optional materials for new diaphragms. However, polysulfone polymers are mostly hydrophobic substances. As diaphragm materials, they will produce large diaphragm resistance in aqueous solutions, and further improvement is still needed to meet application requirements.
[0005] Patent application CN116200779A discloses a composite diaphragm for alkaline water electrolysis and its preparation method and application. The composite diaphragm for alkaline water electrolysis comprises a cortex, a finger-shaped porous layer and a three-dimensional porous layer connected in sequence; wherein the three-dimensional porous layer contains a support body; the invention adopts a special heterogeneous structure design of the cortex, the finger-shaped porous layer and the three-dimensional porous layer, which can not only obtain an alkaline water electrolysis diaphragm with an ultra-high bubble point, but also the diaphragm has extremely low surface resistance, hydrophilicity and ultra-fast wettability; wherein the support body is arranged in the three-dimensional porous layer to effectively enhance the mechanical strength of the diaphragm for alkaline water electrolysis; Patent application CN 114432905A discloses a non-asbestos alkaline water electrolysis composite diaphragm and a preparation method thereof. The steps taken in the application are as follows: (1) preparation of casting solution; (2) preparation of polysulfone / zirconium dioxide composite diaphragm; (3) post-treatment of polysulfone / zirconium dioxide composite diaphragm; the invention uses highly alkali-resistant polysulfone resin and polymer reinforcing agent as polymers; zirconium dioxide is used to hydrophilically modify the polymer. The addition of ZrO can improve the hydrophilicity of the polymer, thereby effectively reducing the surface resistance and improving the current efficiency. However, when the porogen content in the above two patent applications is too high, it will cause pore collapse and defects, affecting the stability of the diaphragm.
[0006] Patent application CN115896863B discloses an ultra-thin composite diaphragm for alkaline water electrolysis containing nanofibers such as polypropylene fibers. The composite diaphragm is composed of a porous support layer and a dense cortex formed on the outer surface of the porous support layer. The porous support layer and the dense cortex are prepared from a slurry of the same composition. The slurry includes nanofibers, inorganic nanoparticles, organic high molecular polymers and a binder. The mass percentage S% of the nanofibers in the slurry satisfies the length L and diameter D of the nanofibers: S=K*√L / D. The application introduces nanofibers to reduce the resistance value of the diaphragm by reducing the thickness of the diaphragm while maintaining good mechanical strength. However, the diaphragm does not contain ion-conducting functional groups, and interface incompatibility is prone to occur between different materials, which is not conducive to the effective transfer of ions, and its ion conduction efficiency is relatively low. Summary of the invention
[0007] In order to overcome the shortcomings of the prior art, the present invention aims to provide a high-performance polysulfone fiber composite membrane and a preparation method thereof. The introduction of imidazole groups and quaternary ammonium groups provides OH groups of the composite membrane. - The block copolymer structure is conducive to the formation of hydrophilic and hydrophobic microphase separation. The hydrophilic ends are connected to form ion transfer channels, and the hydrophobic ends serve as skeleton supports to ensure the dimensional stability and mechanical properties of the composite membrane. At the same time, the ordered structure formed by the electrospinning process further enhances the ion conduction performance in the membrane, and at the same time enhances the alkali resistance stability and mechanical properties of the membrane. It achieves both high OH -Preparation of composite diaphragms for hydrogen production by water electrolysis with advantages of high root ion conductivity, high gas barrier properties, high mechanical stability and high alkali corrosion resistance.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A high-performance polysulfone fiber composite diaphragm is composed of an ordered nanofiber layer containing functionalized polysulfone polymers and polysulfone block copolymers and a dense component filled in the gaps and surface of the ordered nanofiber layer.
[0010] Calculated by the mass fraction of raw materials, the ratio of ordered nanofiber layer to dense component is (40-65) parts: (35-60) parts.
[0011] Calculated by weight of raw materials, in the ordered nanofiber layer, the functionalized polysulfone polymer and the polysulfone block copolymer are (10-15) parts: (10-15) parts.
[0012] The dense component is composed of hydrophilic nanoparticles and polysulfone block copolymers. Calculated by the mass fraction of the raw materials, the ratio of the hydrophilic nanoparticles to the polysulfone block copolymers is (75-90) parts: (10-25) parts.
[0013] The functionalized polysulfone polymer is a mixture of one or more of polysulfone, polyethersulfone and polyarylethersulfone modified by imidazole functionalization or quaternary ammonium functionalization in any ratio;
[0014] The polysulfone block copolymer comprises a hydrophobic block A and a hydrophilic block B, wherein the ratio of the hydrophobic block A to the hydrophilic block B is (50-80) parts:(20-50) parts by weight, the hydrophobic block A is a polysulfone polymer, and the hydrophilic block B is a mixture of one or more of polyethylene glycol, polyethylene glycol monomethyl ether, polymethacrylate, polyvinyl alcohol, polypropylene alcohol, and polyacrylic acid in any ratio;
[0015] The polysulfone block copolymer is prepared by a condensation polymerization method or a living polymerization method, and the different composition segments enable the polysulfone block copolymer to have microphase separation ability.
[0016] A method for preparing a high-performance polysulfone fiber composite diaphragm comprises the following steps:
[0017] Step S1, dissolving the functionalized polysulfone polymer and the polysulfone block copolymer in an organic solvent, and stirring to form a uniform spinning solution;
[0018] Step S2, electrospinning the spinning solution in step S1 to obtain an ordered nanofiber layer, drying it in an oven to remove residual solvent, and then performing a hot pressing treatment;
[0019] Step S3, dissolving the hydrophilic inorganic nanoparticles and the polysulfone block copolymer in a glycol / water mixed solvent to prepare a filling liquid;
[0020] Step S4, immersing the ordered nanofiber layer in step S2 in the filling liquid in step S3 for filling, and increasing the penetration of the filling liquid into the fiber layer by repeated decompression and filtration;
[0021] Step S5, washing and drying the composite material in step S4 to obtain an alkaline composite diaphragm material with a dense surface.
[0022] In the step S1, the functionalized polysulfone polymer: the polysulfone block copolymer: the organic solvent are (10-15) parts: (10-15) parts: (75-80) parts, calculated by weight of the raw materials.
[0023] The functionalized polysulfone polymer in step S1 is a mixture of one or more of polysulfone, polyethersulfone and polyarylethersulfone modified by imidazole functionalization or quaternary ammonium functionalization in any ratio.
[0024] The polysulfone block copolymer in step S1 and step S3 comprises a hydrophobic block A and a hydrophilic block B; the ratio of the hydrophobic block A to the hydrophilic block B is (50-80) parts: (20-50) parts by mass, the hydrophobic block A is a polysulfone polymer, and the hydrophilic block B is a mixture of one or more of polyethylene glycol, polyethylene glycol monomethyl ether, polymethacrylate, polyvinyl alcohol, polypropylene alcohol, and polyacrylic acid in any ratio.
[0025] The polysulfone block copolymer in step S1 and step S3 is prepared by polycondensation or living polymerization, and the different composition segments enable the polysulfone block copolymer to have microphase separation ability.
[0026] The organic solvent in step S1 is a mixture of one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, 1,4-dioxane, and dimethyl sulfoxide in any ratio.
[0027] The electrospinning process parameters in step S2 are: an applied electric field of 10-30 kV, a spinning temperature of 20-30° C., a relative humidity of 20-40%, and a spinning receiving distance of 15-30 cm.
[0028] The hot pressing in step S2 refers to compressing the ordered nanofiber layer obtained by electrospinning at a temperature of 30-70° C. and a pressure of 1-5 MPa for 30-300 seconds.
[0029] The hydrophilic inorganic nanoparticle content of the filling liquid in step S3 accounts for 20-50% of the filling liquid mass; the polysulfone block copolymer content accounts for 5-10% of the filling liquid mass; the rest is ethylene glycol / water mixed solvent, in which ethylene glycol: water is (40-50) parts: (50-60) parts.
[0030] The hydrophilic inorganic nanoparticles in step S3 are selected from one or more of zirconium oxide, titanium oxide, cerium oxide, yttrium oxide, strontium titanate, barium titanate, zirconium hydroxide, and magnesium hydroxide in any ratio, and have a particle size of 50-200 nm.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The present invention adopts electrospinning technology to induce the formation of a long-range ordered nanofiber structure during the electrospinning process, thereby promoting the connection of OH- ion transfer channels; at the same time, the skeleton structure of the nanofiber helps to enhance the alkali resistance stability and mechanical properties of the diaphragm material;
[0033] 2. The polysulfone block copolymer structure introduced in the present invention is conducive to the formation of hydrophilic-hydrophobic microphase separation morphology. The hydrophobic end serves as a skeleton support to ensure the dimensional stability and mechanical stability of the diaphragm, and the hydrophilic ends are interconnected to form a penetrating OH- ion transfer channel, further enhancing the transmission of ions;
[0034] 3. The filling liquid used in the present invention contains rich polysulfone block copolymers, which are one of the raw materials for forming nanofibers. By utilizing the difference in solubility for filling, a dense structure can be formed while maintaining the intrinsic structure of the fiber, and the interface compatibility between the fiber and the filling matrix can be enhanced, so that the OH- ion transfer channel is connected over a long distance.
[0035] In summary, compared with the prior art, the present invention adopts electrospinning technology and introduces a polysulfone block copolymer structure, which can promote the connection of OH- ion transfer channels, enhance ion transmission, and achieve both high OH - Preparation of composite diaphragms with advantages such as ion conductivity, high gas barrier properties, high mechanical stability, and high alkali corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The present invention provides a flow chart for preparing the composite diaphragm.
[0037] Figure 2 This is a SEM image of the composite diaphragm in Example 1 provided by the present invention, wherein: Figure 2 (a) Surface morphology of ordered nanofiber layer prepared by electrospinning. Figure 2 (b) is the surface morphology of the ordered nanofiber layer after hot pressing. Figure 2 (c) is the surface morphology of the final composite membrane. DETAILED DESCRIPTION
[0038] The specific embodiments of the present invention are described in detail below in conjunction with the technical solutions and drawings.
[0039] like Figure 1 As shown, a high-performance polysulfone fiber composite diaphragm material is composed of an ordered nanofiber layer containing functionalized polysulfone polymers and polysulfone block copolymers and a dense component filled in the gaps and surface of the ordered nanofiber layer.
[0040] A method for preparing a high-performance polysulfone fiber composite diaphragm comprises the following steps:
[0041] Step S1, dissolving the functionalized polysulfone polymer and the polysulfone block copolymer in an organic solvent, and stirring to form a uniform spinning solution;
[0042] Step S2, electrospinning the spinning solution in step S1 to obtain an ordered nanofiber layer, drying it in an oven to remove residual solvent, and then performing a hot pressing treatment;
[0043] Step S3, dissolving the hydrophilic inorganic nanoparticles and the polysulfone block copolymer in a glycol / water mixed solvent to prepare a filling liquid;
[0044] Step S4, immersing the ordered nanofiber layer in step S2 in the filling liquid in step S3 for filling, and increasing the penetration of the filling liquid into the fiber layer by vacuum filtration to improve the gas barrier performance of the ordered nanofiber layer;
[0045] Step S5, washing and drying the composite material in step S4 to obtain an alkaline composite diaphragm material with a dense surface.
[0046] Example 1
[0047] The present embodiment provides a high-performance polysulfone fiber composite diaphragm, which is composed of an ordered nanofiber layer containing functionalized polysulfone polymers and polysulfone block copolymers, and a dense component filling the gaps and surfaces of the ordered nanofiber layer; wherein, calculated by weight of the raw materials, the ratio of the ordered nanofiber layer to the dense component is 55 parts:45 parts; the dense component is composed of hydrophilic nanoparticles and polysulfone block copolymers, and calculated by weight of the raw materials, the ratio of the hydrophilic nanoparticles to the polysulfone block copolymers is 79 parts:21 parts.
[0048] The preparation method is as follows:
[0049] Step S1, dissolving imidazole functionalized polysulfone and polysulfone-polyethylene glycol block copolymer in N,N-dimethylacetamide, stirring to form a uniform spinning solution, wherein the functionalized polysulfone polymer: polysulfone block copolymer: organic solvent are 12 parts: 10 parts: 78 parts by weight of the raw materials, and the polysulfone: polyethylene glycol in the polysulfone-polyethylene glycol block copolymer are 70 parts: 30 parts by weight;
[0050] Step S2, electrospinning the spinning solution in step S1 to obtain an ordered nanofiber layer, the electrospinning parameters are: an external electric field of 20 kV, a temperature of 25° C., a relative humidity of 30%, a spinning receiving distance of 18 cm, the ordered nanofiber layer is placed in an oven to dry, and then hot-pressed at 40° C. and 2 MPa for 120 s;
[0051] Step S3, dissolving zirconium oxide and polysulfone-polyethylene glycol block copolymer in a mixed solvent of ethylene glycol / water and heating to dissolve to prepare a filling liquid, wherein the mixed solvent contains ethylene glycol and water in a ratio of 50 parts:50 parts, wherein the zirconium oxide content accounts for 30% of the filling liquid mass, the particle size is 150 nm, the polysulfone block copolymer content accounts for 8% of the filling liquid mass, and the polysulfone-polyethylene glycol block copolymer is the same as that in step S1;
[0052] Step S4, immersing the ordered nanofiber layer in step S2 in the filling liquid in step S3 for filling, and increasing the penetration of the filling liquid into the fiber layer by repeated decompression and filtration.
[0053] Step S5: Wash and dry the composite material in step S4 to obtain a surface-dense alkaline composite diaphragm material, the microscopic morphology of which is as follows: Figure 2 shown.
[0054] Example 2
[0055] The present embodiment provides a high-performance polysulfone fiber composite diaphragm, which is composed of an ordered nanofiber layer containing functionalized polysulfone polymers and polysulfone block copolymers and a dense component filling the gaps and surfaces of the ordered nanofiber layer; wherein, calculated by weight of the raw materials, the ratio of the ordered nanofiber layer to the dense component is 50 parts:50 parts; the dense component is composed of hydrophilic nanoparticles and polysulfone block copolymers, and calculated by weight of the raw materials, the ratio of the hydrophilic nanoparticles to the polysulfone block copolymers is 85 parts:15 parts.
[0056] The preparation method is as follows:
[0057] Step S1, dissolving imidazole functionalized polysulfone and polysulfone-polyvinyl alcohol block copolymer in N,N-dimethylacetamide, stirring to form a uniform spinning solution, wherein the functionalized polysulfone polymer: polysulfone block copolymer: organic solvent are 15 parts: 10 parts: 75 parts by weight of the raw materials, and the polysulfone: polyvinyl alcohol in the polysulfone-polyvinyl alcohol block copolymer is 60:40 parts by weight;
[0058] Step S2, electrospinning the spinning solution in step S1 to obtain an ordered nanofiber layer, the electrospinning parameters are: an external electric field of 20 kV, a temperature of 25° C., a relative humidity of 30%, a spinning receiving distance of 18 cm, the ordered nanofiber layer is placed in an oven to dry, and then hot-pressed at 40° C. and 2 MPa for 120 s;
[0059] Step S3, dissolving zirconium oxide and polysulfone-polyvinyl alcohol block copolymer in a mixed solvent of ethylene glycol / water and heating to dissolve to prepare a filling liquid, wherein the ratio of ethylene glycol to water is 43 parts:57 parts, wherein the content of zirconium oxide accounts for 35% of the mass of the filling liquid, the particle size is 200 nm, the content of polysulfone block copolymer accounts for 6% of the mass of the filling liquid, and the polysulfone-polyvinyl alcohol block copolymer is the same as that in step S1;
[0060] Step S4, immersing the ordered nanofiber layer in step S2 in the filling liquid in step S3 for filling, and increasing the penetration of the filling liquid into the fiber layer by repeated decompression and filtration;
[0061] Step S5, washing and drying the composite material in step S4 to obtain an alkaline composite diaphragm material with a dense surface.
[0062] Example 3
[0063] The present embodiment provides a high-performance polysulfone fiber composite diaphragm, which is composed of an ordered nanofiber layer containing functionalized polysulfone polymers and polysulfone block copolymers, and a dense component filling the gaps and surfaces of the ordered nanofiber layer; wherein, calculated by weight of the raw materials, the ratio of the ordered nanofiber layer to the dense component is 50 parts:50 parts; the dense component is composed of hydrophilic nanoparticles and polysulfone block copolymers, and calculated by weight of the raw materials, the ratio of the hydrophilic nanoparticles to the polysulfone block copolymers is 79 parts:21 parts.
[0064] The preparation method is as follows:
[0065] Step S1, dissolving quaternary ammonium functionalized polysulfone and polysulfone-polyethylene glycol block copolymer in N,N-dimethylacetamide, stirring to form a uniform spinning solution, wherein the functionalized polysulfone polymer: polysulfone block copolymer: organic solvent are 12 parts: 10 parts: 78 parts by weight of the raw materials, and the polysulfone: polyethylene glycol in the polysulfone-polyethylene glycol block copolymer are 80 parts: 20 parts by weight;
[0066] Step S2, electrospinning the spinning solution in step S1 to obtain an ordered nanofiber layer, the electrospinning parameters are: an external electric field of 20 kV, a temperature of 30° C., a relative humidity of 25%, a spinning receiving distance of 15 cm, the ordered nanofiber layer is placed in an oven to dry, and then hot-pressed at 60° C. and 2 MPa for 60 s;
[0067] Step S3, dissolving titanium oxide and polysulfone-polyethylene glycol block copolymer in a mixed solvent of ethylene glycol / water and heating to dissolve to prepare a filling liquid, wherein the ratio of ethylene glycol to water is 50 parts:50 parts, wherein the titanium oxide content accounts for 30% of the filling liquid mass, the particle size is 150 nm, the polysulfone block copolymer content accounts for 8% of the filling liquid mass, and the polysulfone-polyethylene glycol block copolymer is the same as that in step S1;
[0068] Step S4, immersing the ordered nanofiber layer in step S2 in the filling liquid in step S3 for filling, and increasing the penetration of the filling liquid into the fiber layer by repeated decompression and filtration;
[0069] Step S5, washing and drying the composite material in step S4 to obtain an alkaline composite diaphragm material with a dense surface.
[0070] Example 4
[0071] The present embodiment provides a high-performance polysulfone fiber composite diaphragm, which is composed of an ordered nanofiber layer containing functionalized polysulfone polymers and polysulfone block copolymers and a dense component filling the gaps and surfaces of the ordered nanofiber layer; wherein, calculated by weight of the raw materials, the ratio of the ordered nanofiber layer to the dense component is 55 parts:45 parts; the dense component is composed of hydrophilic nanoparticles and polysulfone block copolymers, and calculated by weight of the raw materials, the ratio of the hydrophilic nanoparticles to the polysulfone block copolymers is 81 parts:19 parts.
[0072] The preparation method is as follows:
[0073] Step S1, dissolving imidazole functionalized polyethersulfone and polysulfone-polyethylene glycol block copolymer in N,N-dimethylacetamide, stirring to form a uniform spinning solution, wherein the functionalized polysulfone polymer: polysulfone block copolymer: organic solvent are 12 parts: 10 parts: 78 parts by weight of the raw materials, and the polysulfone: polyethylene glycol in the polysulfone-polyethylene glycol block copolymer are 70 parts: 30 parts by weight;
[0074] Step S2, electrospinning the spinning solution in step S1 to obtain an ordered nanofiber layer, the electrospinning parameters are: external electric field 20 kV, temperature 25° C., relative humidity 25%, spinning receiving distance 15 cm, the ordered nanofiber layer is placed in an oven to dry, and then hot pressed at 40° C. and 2 MPa for 120 s;
[0075] Step S3, dissolving cerium oxide and polysulfone-polyethylene glycol block copolymer in a mixed solvent of ethylene glycol / water and heating to dissolve to prepare a filling liquid, wherein the ratio of ethylene glycol to water is 45 parts:55 parts, wherein the content of cerium oxide accounts for 35% of the mass of the filling liquid, the particle size is 50 nm, the content of polysulfone block copolymer accounts for 8% of the mass of the filling liquid, and the polysulfone-polyethylene glycol block copolymer is the same as that in step S1;
[0076] Step S4, immersing the ordered nanofiber layer in step S2 in the filling liquid in step S3 for filling, and increasing the penetration of the filling liquid into the fiber layer by repeated decompression and filtration;
[0077] Step S5, washing and drying the composite material in step S4 to obtain an alkaline composite diaphragm material with a dense surface.
[0078] Comparative Example 1
[0079] The materials and input ratios used in this comparative example are the same as those in Example 1, except that the composite diaphragm in Comparative Example 1 is prepared by blending and casting various materials.
[0080] Performance Testing
[0081] The performance of different composite diaphragms was tested, and the results are shown in the following table:
[0082]
[0083]
[0084] The test results show that the OH - The ion conductivity is about 1.5 times that of the blended cast composite membrane with the same material, indicating that the ordered nanofiber layer formed by the electrospinning process has a long-range ordered ion transfer channel, and the ion conductivity of the composite membrane is significantly improved. At the same time, the ordered three-dimensional fiber network structure can serve as a skeleton to support the composite membrane, further improving the mechanical strength of the composite membrane.
Claims
1. A high-performance polysulfone fiber composite diaphragm, characterized in that: It is composed of an ordered nanofiber layer containing functionalized polysulfone polymers and polysulfone block copolymers and a dense component filled in the gaps and surface of the ordered nanofiber layer; Calculated by weight of raw materials, the ratio of ordered nanofiber layer: dense component is (40-65) parts: (35-60) parts; Calculated by weight of the raw materials, in the ordered nanofiber layer, the functionalized polysulfone polymer and the polysulfone block copolymer are (10-15) parts: (10-15) parts; The dense component is composed of hydrophilic nanoparticles and polysulfone block copolymers. Calculated by the mass fraction of the raw materials, the ratio of the hydrophilic nanoparticles to the polysulfone block copolymers is (75-90) parts: (10-25) parts.
2. A high-performance polysulfone fiber composite diaphragm according to claim 1, characterized in that: The functionalized polysulfone polymer is a mixture of one or more of polysulfone, polyethersulfone and polyarylethersulfone modified by imidazole functionalization or quaternary ammonium functionalization in any ratio; The polysulfone block copolymer comprises a hydrophobic block A and a hydrophilic block B, wherein the ratio of the hydrophobic block A to the hydrophilic block B is (50-80) parts:(20-50) parts by weight, the hydrophobic block A is a polysulfone polymer, and the hydrophilic block B is a mixture of one or more of polyethylene glycol, polyethylene glycol monomethyl ether, polymethacrylate, polyvinyl alcohol, polypropylene alcohol, and polyacrylic acid in any ratio; The polysulfone block copolymer is prepared by a condensation polymerization method or a living polymerization method, and the different composition segments enable the polysulfone block copolymer to have microphase separation ability.
3. A method for preparing a high-performance polysulfone fiber composite diaphragm, characterized in that: The following steps are involved: Step S1, dissolving the functionalized polysulfone polymer and the polysulfone block copolymer in an organic solvent, and stirring to form a uniform spinning solution; Step S2, electrospinning the spinning solution in step S1 to obtain an ordered nanofiber layer, drying it in an oven to remove residual solvent, and then performing a hot pressing treatment; Step S3, dissolving the hydrophilic inorganic nanoparticles and the polysulfone block copolymer in a glycol / water mixed solvent to prepare a filling liquid; Step S4, immersing the ordered nanofiber layer in step S2 in the filling liquid in step S3 for filling, and increasing the penetration of the filling liquid into the fiber layer by repeated decompression and filtration; Step S5, washing and drying the composite material in step S4 to obtain an alkaline composite diaphragm material with a dense surface.
4. The method for preparing a high-performance polysulfone fiber composite diaphragm according to claim 3, characterized in that: In the step S1, the functionalized polysulfone polymer: the polysulfone block copolymer: the organic solvent are (10-15) parts: (10-15) parts: (75-80) parts, calculated by weight of the raw materials; The functionalized polysulfone polymer in step S1 is a mixture of one or more of imidazole-functionalized or quaternary ammonium-functionalized polysulfone, polyethersulfone, and polyarylethersulfone in any ratio; The polysulfone block copolymer in step S1 and step S3 comprises a hydrophobic block A and a hydrophilic block B; the ratio of the hydrophobic block A to the hydrophilic block B is (50-80) parts: (20-50) parts by weight, the hydrophobic block A is a polysulfone polymer, and the hydrophilic block B is a mixture of one or more of polyethylene glycol, polyethylene glycol monomethyl ether, polymethacrylate, polyvinyl alcohol, polypropylene alcohol, and polyacrylic acid in any ratio; The polysulfone block copolymer in step S1 and step S3 is prepared by polycondensation or living polymerization, and the different composition segments enable the polysulfone block copolymer to have microphase separation ability.
5. The method for preparing a high-performance polysulfone fiber composite diaphragm according to claim 3, characterized in that: The organic solvent in step S1 is a mixture of one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, 1,4-dioxane, and dimethyl sulfoxide in any ratio.
6. The method for preparing a high-performance polysulfone fiber composite diaphragm according to claim 3, characterized in that: The electrospinning process parameters in step S2 are: an applied electric field of 10-30 kV, a spinning temperature of 20-30° C., a relative humidity of 20-40%, and a spinning receiving distance of 15-30 cm.
7. The method for preparing a high-performance polysulfone fiber composite diaphragm according to claim 3, characterized in that: The hot pressing in step S2 refers to compressing the ordered nanofiber layer obtained by electrospinning at a temperature of 30-70° C. and a pressure of 1-5 MPa for 30-300 seconds.
8. The method for preparing a high-performance polysulfone fiber composite diaphragm according to claim 3, characterized in that: In step S3, the content of hydrophilic inorganic nanoparticles in the filling liquid is 20-50% of the mass of the filling liquid; the content of polysulfone block copolymer is 5-10% of the mass of the filling liquid; the rest is ethylene glycol / water mixed solvent, in which the mixed solvent is (40-50) parts of ethylene glycol and (50-60) parts of water, calculated by the mass fraction of the raw materials; The hydrophilic inorganic nanoparticles in step S3 are selected from one or more of zirconium oxide, titanium oxide, cerium oxide, yttrium oxide, strontium titanate, barium titanate, zirconium hydroxide, and magnesium hydroxide in any ratio, and have a particle size of 50-200 nm.
Citation Information
Patent Citations
Ultrathin composite membrane for alkaline water electrolysis, its preparation method, and alkaline water electrolysis device
CN115896863B
Composite diaphragm for alkaline water electrolysis as well as preparation method and application of composite diaphragm
CN116200779A
Cited By
Alkaline electrolyzed water composite diaphragm based on hydroxyl alumina and preparation method of alkaline electrolyzed water composite diaphragm
CN121556087A